(untitled) (Research, Society and Development, 2022)
The post-traumatic stress disorder is one of the main consequences in victims of childhood sexual abuse, and it’s symptoms are involved in many cognitive-behavioral implications for those subjects. Reseachs suggest that these symptoms are the expression of morphological and physiological modifications in the brain structure of the victims, compared to people who didn’t suffer this trauma. The present scoping review aims to answer which are the most relevant alterations studied in the current literature. Methods: A scoping review was conducted by searching the Capes Periodicals and PubMed databases. Seven texts that answered the guiding were selected and used as the basis for this review, which met the following selection criteria: publications dated from 2016 to 2021, deletion of duplicate articles and those that did not address the relationship between post-traumatic stress disorder, childhood sexual abuse and the associated neurological consequences. Results: 7 publications were included in our study. Individuals who have suffered abuse in childhood, including sexual abuse, presented some alteration in brain regions, such as changes in volume, functional connectivity and biochemical composition. Conclusion: Substantial structural and chemical modifications can be observed in the brain of individuals with PTSD that had childhood sexual abuse as the motivation to the trauma.